INSTALASI THERMOELECTRIC GENERATOR UNIT SEBAGAI PEMBANGKIT LISTRIK UTAMA DI PECIKO PLATFORM LAPANGAN SENIPAH TERMINAL (STUDI KASUS DI PERUSAHAAM PT.PERTAMINA HULU MAHAKAM) - Heri Cahyono; Rachmasari Pramita Wardhani; Dullen Arkadius (Mechanical Engineering Departement - Universitas Tridharma, 2021)
Thermoelectric Generator produces electrical power through the direct conversion of heat energy into electrical energy. It operates on the same principle as the thermocouples that are used for measuring temperatures and in safety shutoff controls for gas water heaters, home furnaces, etc. However, the TEG utilizes semiconducting thermoelectric materials that are much more efficient and thus permit practical thermoelectric power sources. A thermocouple consists of two dissimilar materials (usually in wire form) which are joined together at one end. If this junction is heated to a higher temperature than the other end of the wire, a voltage will exist across the cooler end. Further, electrical power will be delivered to a load placed in the circuit. This process will continue provided that the temperature difference is maintained. A THEG is a system which provides the means to maintain these required conditions. Key Words : thermoelectric, generator, power plant, installation